Equipping Organizational Reliability: Between Organization and Situated Activity, the Contribution of Situational Approaches - Stéphanie Gentil (M@n@gement)
Research on high-reliability organizations (HROs) studies how organizations subject to significant risks manage to maintain their reliability. In such work, reliability is not based exclusively on an organization’s ability to anticipate and prevent problems but is the product of interactions between actors adjusting to unexpected events every day. By focusing primarily on communicative and cognitive processes, HROs neglect the role of equipment in supporting the construction of organizational reliability. We argue that this pitfall arises from the unit of analysis considered by HRO literature, which led us to shift our focus from structure (rules, prevention systems) to situated interactions. We suggest that this should be complemented by a situational analysis framework exploring the theoretical potential of the ‘situation’ concept as an intermediate analysis unit between situated activity and organization. From in situ observation sequences in two operating rooms of a private clinic, we distinguished three types of situations. Here, the entwinement of human activities with equipment that builds reliability takes different forms: standard, bounded, and extended situations. Finally, our research highlights three contributions of a situational approach to thinking about organizational reliability: (1) as an intermediate notion between the given and the created, the situation enables us to study the tangible and intangible equipment supporting reliability; (2) as an intermediary notion between singularity and regularity, it allows us to highlight the influence of context on reliability maintenance activities; and (3) as an intermediary notion between instantaneity of action and permanence of the organization, it lets us identify reliability maintenance trajectories.